2021
DOI: 10.1177/10443894211008846
|View full text |Cite
|
Sign up to set email alerts
|

Supporting Those Who Love the Loathed: Trauma-Informed Support Groups for Family Members of Registered Sex Offenders

Abstract: Social workers are typically empathic, but it can be challenging to offer compassionate care to those who harmed others and, by extension, to the people who love them. This article describes a trauma-informed support group intervention for family members of individuals required to register as sex offenders (RSOs). We begin with a brief overview of this unique population, review the empirical research exploring family members’ needs and the services available to them, and introduce the trauma-informed framework… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Our study builds on other evaluations of support options for families of sex offenders, which consistently highlights the efficacy of self-help and peer support approaches in promoting coping strategies and resilience (Sample et al, 2018;Kavanagh & Levenson, 2021). However, this article has emphasized the politicized awareness that emerged from women's contact with each other and PartnerSPEAK.…”
Section: Discussionmentioning
confidence: 90%
“…Our study builds on other evaluations of support options for families of sex offenders, which consistently highlights the efficacy of self-help and peer support approaches in promoting coping strategies and resilience (Sample et al, 2018;Kavanagh & Levenson, 2021). However, this article has emphasized the politicized awareness that emerged from women's contact with each other and PartnerSPEAK.…”
Section: Discussionmentioning
confidence: 90%
“…The therapist's ability to hold to the principles elucidated in this article, in particular the role of empathy and compassionate care, can be challenged depending on the social location of group participants, either from a place of prejudice or ignorance. In relation to prejudice, Kavanagh and Levenson (2022) offer a valuable insight into the need to tailor trauma-informed practice skills and tools for facilitating support services for highly stigmatised populations. The parallel problem of ignorance must also be addressed; consequently, cultural competence requires investigation into how best to meet the needs of specific populations.…”
Section: Group Heterogeneity: Working With Unique Populationsmentioning
confidence: 99%
“…An individual whose partner is a political offender could have fewer sensations of disgrace about the partner's detention (Folch, 2021), compared to an individual whose partner is detained for a sex offense. Kavanagh and Levenson (2021) reported that the latter sustained substantial damage. Evans et al (2021) also reported that the travesty of a felony charge is significantly more pronounced among relatives of sex offenders than among relatives of other offenders.…”
Section: Non-incarcerated Partners' Feelingsmentioning
confidence: 99%